Are there distinct forms of accelerated forgetting and, if so, why?. (January 2019) - Mayes, Andrew R.; Hunkin, Nicola M.; Isaac, Claire; Muhlert, Nils
Abstract: Whether accelerated long-term forgetting (ALF) and classic organic amnesia, particularly hippocampal-amnesia, differ qualitatively or merely quantitatively is disputed. Qualitative difference accounts postulate that ALF patients show normal recall memory for at least minutes, during which hippocampal-amnesics already show accelerated forgetting and impaired recall but, thereafter, ALF patients show accelerated forgetting and impaired delayed recall. These delayed impairments may be more severe than those shown by hippocampal-amnesics. In contrast, quantitative difference accounts postulate that ALF patients merely have mild hippocampal-amnesia, so their later forgetting rates and recall levels are sub-normal but always better than those of hippocampal-amnesics with worse initial recall levels (i.e., there is no cross-over in forgetting rates at longer delays). Many ALF studies in people with epilepsy have demonstrated evidence of a single dissociation–with accelerated delayed forgetting relative to healthy controls. Even when initial recall seems genuinely normal, uncompromised by patients needing more learning trials or showing below-average performance on more demanding recall tests, without further evidence, a quantitative interpretation remains possible. Resolution of the dispute requires evidence of a double dissociation between ALF patients and hippocampal-amnesics with more impaired initial recall in a comparison also involving matched controls. The only two studies that have made this comparison found that there was a cross–over interaction between initial and delayed recall in the ALF and amnesic patients, inconsistent with quantitative difference accounts. The functional and pathological conditions underlying this cross-over effect need to be systematically explored, controlling for potential methodological confounds, in temporal lobe epilepsy and transient epileptic amnesia as well as non-epileptic conditions. Future research must also explore under what conditions, if any, milder hippocampal-amnesics show relatively normal delayed forgetting of recall, and for how long, if at all, ALF patients show completely normal recall. Relatedly, the functional and pathological heterogeneity of ALF needs systematic exploration.